Livelihood diversification in rural Andhra Pradesh - Fenn, B; Galab, S; Jones, N; Wilson, I; Raju, D (http://www.younglives.org.uk/publications/working-papers, 2006)
Livelihood diversification is the process by which households maintain diverse activities and assets in order to survive and to improve their standard of living. To ensure effective interventions to reduce rural poverty and vulnerability to poverty, it is important to understand household diversification strategies and the extent to which such strategies are feasible. In Andhra Pradesh, this topic is of particular relevance given the recent agricultural crisis in the state, resulting in the suicides of hundreds of farmers. After years of relative neglect under the previous state government, the current government of Andhra Pradesh is focusing on improving the agricultural sector and reformulating policies to better address the needs of farmers. Agriculture remains the main activity in rural Andhra Pradesh, particularly among poor households. Using Young Lives data from 20 sites across Andhra Pradesh, this paper presents an analysis of household diversification patterns and examines the links between household assets and livelihood diversification. The findings here demonstrate that, in order to help households move out of poverty, greater opportunities to engage in non-farming activities are needed. The authors discuss the links between poverty and education, asset ownership, and access to land and infrastructure, and outline conclusions and implications for policy. These findings underscore the urgency of the agricultural crisis in Andhra Pradesh, and the need to find a holistic solution to tackle the decline of this sector of the state economy.